Comparative study on the efficiency of motor rehabilitation of the lower limbs using a stationary horizontal bicycle versus a standard therapeutic program (Balneo and PRM Research Journal, 2022)
The purpose of the present study is to compare the efficiency of two physiotherapeutic programs for rehabilitation of the lower limbs, one using a stationary bicycle and the other one being a standard program, targeting muscle imbalance deficit. Subjects are outpatients - the control group (C n=5), 58.67 ± 11.67 years, received a standard rehabilitation program, and the experimental group (E n=5), 56.67 ± 12.14 years, received a proposed rehabilitation program implying a stationary bicycle. Equipment used is for muscle imbalances – sensor attached to bicycle pedals, for joint testing – goniometer, for heart rate smart watch, pain assessment – VAS numeric scale, and for perceived effort Borg scale. The rehabilitation program including the stationary horizontal bicycle obtained better results in terms of pain control (T-Test p C/E=.004/.001 and Wilcoxon p C/E=.039/.041) and the correction of muscular imbalances (T-Test p C/E=.003/.000, r= .990/.997) related to the lower limbs, with the mention that both programs recorded statistically significant results regarding functionality. HR values for the control group and experimental group < THR values, aerobic conditioning with the submaximal effort being essential for rehabilitation. Both programs maintained the same perceived level of effort with an average of 3.6 Borg- moderate effort, respectively mild-moderate dyspnea.